2022
DOI: 10.1007/s10340-022-01578-1
|View full text |Cite
|
Sign up to set email alerts
|

First detection of resistance to deltamethrin in Spanish populations of the Mediterranean fruit fly, Ceratitis capitata

Abstract: The control of the Mediterranean fruit fly (Medfly), Ceratitis capitata, in citrus orchards in Spain is mainly based in three insecticides (spinosad, lambda-cyhalothrin and deltamethrin) and the liberation of sterile males. However, Medfly control is compromised by the development of lambda-cyhalothrin resistance and the detection of spinosad-resistant alleles in field populations. We report here, for the first time, resistance to deltamethrin in populations collected in fields under different management strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Previous studies have also reported significantly reduced r and Ro in pyrethroid-resistant M. domestica, C. includens, C. capitata, Anopheles funestus Giles, Ae. aegypti, P. papatasi, and O. hyalinipennis compared with their pyrethroid-susceptible counterparts [29,59,61,62,65,67,68]. Additionally, s xj , m x , l x m x , e xj , and v xj were markedly reduced in Alpha-RS M. domestica compared with Alpha-SS M. domestica, indicating fitness costs associated with alpha-cypermethrin resistance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have also reported significantly reduced r and Ro in pyrethroid-resistant M. domestica, C. includens, C. capitata, Anopheles funestus Giles, Ae. aegypti, P. papatasi, and O. hyalinipennis compared with their pyrethroid-susceptible counterparts [29,59,61,62,65,67,68]. Additionally, s xj , m x , l x m x , e xj , and v xj were markedly reduced in Alpha-RS M. domestica compared with Alpha-SS M. domestica, indicating fitness costs associated with alpha-cypermethrin resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have also detected fitness costs in different insecticide-resistant strains, such as M. domestica [29,31,[56][57][58], Phlebotomus papatasi (Scopoli) [59], Ae. aegypti [60,61], O. hyalinipennis [62,63], Plutella xylostella L. [64], Chrysodeixis includens Walker [65], Rhopalosiphum padi L. [66], and Ceratitis capitata (Wiedemann) [67].…”
Section: Discussionmentioning
confidence: 99%